Aberrant DNA methylation of SOCS1 gene is not associated with resistance to imatinib mesylate among chronic myeloid leukemia patients - Elias M.H.; Azlan H.; Baba A.A.; Ankathil R. (Bentham Science Publishers B.V., 2024)
Indexed by SCOPUS